Providing Students an Aural Learning Modality With Written Grammar Feedback for Their Writing - Bradhiansyah Tri Suryanto (International Journal of English Education and Linguistics (IJoEEL), 2021)
The study successfully investigates how students' writing abilities are affected by feedback on written grammar that is specifically customized to their auditory learning preferences. It was designed to find a better method for enhancing auditory learners' writing skills. The results show that tailored grammatical feedback that takes into account auditory learning preferences produces better results in improving writing abilities than traditional input. When given individualized feedback, auditory learners improved their writing skills more. The study highlights the value of teaching approaches that take into account students' chosen styles of learning, especially when it comes to developing writing abilities. It advises using tactics that are in line with learners' preferences into educational design. The study opens the door for future research into alternate ways that make use of adaptable methods and educational technology to improve student learning. Longitudinal studies can also shed light on the long-term effects of tailored learning strategies that are in line with student preferences. In parallel, the larger educational community studies how various learning styles and pedagogies interact. By continuously enhancing curricula and teaching methods, this study helps to maximize achievement in a variety of educational environments. Overall, this study offers implications for enhancing educational procedures and encouraging top-notch student achievement